The relationship between internal intangible factors and SME's sustainable growth: mediated by competitive advantage and advisory engagement as a moderator - Tairuddin Yusoff (2019)
The importance of Small and Medium Enterprises (SMEs) towards the economic development of every nation of the world is well acknowledged by the stakeholders. In Malaysia the government has developed and promoted various support programs for the development of SMEs. Despite the efforts, SMEs in Malaysia are not able to sustain their growth as manifested by the lower contributions towards the GDP compared to other nations. This study was undertook to determine the micro foundations for SMEs to achieve sustainable growth that refers to the continuous and maintainable growth from the economic perspectives of financial, quality, environment and social aspects of SMEs. From the main theoretical perspectives in relation to the SMEs’ sustainable growth based on the ontological layers of SMEs, four predictor variables were identified with growth intention at entrepreneur level; both dynamic capabilities and organisational culture at enterprise level and networking capabilities at the network level. Underpinned by the Resource-Based Value of the firm, a theoretical framework combining all the four variables was developed to study their relationships with sustainable growth of SMEs with competitive advantage and advisory engagement as the mediating and moderating factor respectively. After a successful pilot study to determine the reliability of the measurement, data collection was done. Guided by the lens of positivist paradigm, the methodological approach of this study was quantitative; non-experimental descriptive research survey with structured questionnaires using cross sectional samples. A total of 267 usable samples were collected from the defined group of private limited (Sendirian Berhad) companies registered with Companies Commission of Malaysia (SSM) and SME Corporation of Malaysia, and importantly are more than five years in operations, to represent sustainable growth of SMEs. Using PLS-SEM, the data revealed that all the four internal intangible predictor variables were positively and significantly affecting sustainable growth of SMEs. The main findings of this study are the significant effect of growth intention of the entrepreneur towards achieving sustainable growth which has not been within the radar of many current researches, and also the influence of perceived control on growth intention through spousal support. It was also found that competitive advantage partially mediated those relationships. However, there was no moderating effect of advisory engagement on the sustainable growth of SMEs. Contributions to the body of knowledge both theoretically and methodologically were put forth. This study has provided empirical evidences on the effect of the four fundamental factors on the multi-dimensions of sustainable growth in one overarching and complete framework for xiii sustainable growth of SMEs particularly in Malaysia. Nonetheless it is recommended to have more conversations from various management fields to further extend these findings in different cultural and other contextual settings.